Asymmetric Trilayer All‐Polymer Dielectric Composites with Simultaneous High Efficiency and High Energy Density: A Novel Design Targeting Advanced Energy Storage Capacitors. (23rd June 2021) - Sun, Liang; Shi, Zhicheng; He, Benlin; Wang, Huanlei; Liu, Shuai; Huang, Minghua; Shi, Jing; Dastan, Davoud; Wang, Hong
Abstract: Polymeric dielectrics have attracted intensive attention worldwide because of their huge potential for advanced energy storage capacitors. Thus far, various effective strategies have been developed to improve the inherent low energy densities of polymer dielectrics. However, enhanced energy density is always accompanied by suppressed discharge efficiency, which is detrimental to practical applications and deserves considerable concern. Targeting at achieving simultaneous high energy density and high discharge efficiency, the unique design of asymmetric all‐polymer trilayer composite consisting of a transition layer sandwiched by a linear dielectric layer and a nonlinear dielectric layer is herein reported. It is demonstrated that the nonlinear dielectric layer offers high energy density, while the linear dielectric layer provides high discharge efficiency. Especially, the transition layer can effectively homogenize the electric field distribution, resulting in greatly elevated breakdown strength and improved energy density. In particular, a high efficiency of 89.9% along with a high energy density of 12.15 J cm −3 are concurrently obtained. The asymmetric trilayer all‐polymer design strategy represents a new way to achieve high‐performance dielectric energy storage materials. Abstract : The unique design of an asymmetric all‐polymer trilayer composite consisting of a transition layer sandwiched by a linear dielectric layer and a nonlinear dielectric layer is developed. It is demonstrated that this design strategy is capable of homogenizing electric fields, yielding ultrahigh breakdown strengths (>690 kV mm −1 ), ultrahigh efficiencies (>88%), and high energy densities (>10 J cm −3 ).